F. Faktor Faktor-faktor yang berhubungan dengan kejadian stunting pada balita usia 24-59 bulan di wilayah kerja puskesmas jambula tahun 2022 - Sumaga, Sakila Setiawati; Suharto; Agustin Rahayu (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
ABSTRACT The health indicator that assesses the success of achievement of the SDGs is the nutritional status of children under five. Toddlers are a group that is vulnerable to malnutrition, one of which is stunting. Stunting is a condition that describes toddlers as having a body length or height that is less than their age; this condition uses a length or size that is <2 SD. Stunting toddlers in the future will experience difficulties, one of which is achieving optimal physical and cognitive development. This study determines the factors associated with stunting in toddlers aged 24-59 months in the Jambula Health Center Working Area in 2022. This type of research uses a quantitative analytic design with a cross-sectional study design. The population in this study was 285 toddlers aged 24-59 months. The sample size used was 74 toddlers. The sample used a stratified random sampling method with a systematic random sampling technique. The study's results showed a relationship between a history of infectious disease (p=0.002) and the incidence of stunting. There was no relationship between LBW (p=0.463) and exclusive breastfeeding (p=0.560) with the incidence of stunting. The recommendation to mothers with toddlers under five years old is to increase awareness about toddler health, especially about the fulfillment of toddler nutrition. Mothers can prevent stunting and routinely visit health services to get early detection of toddler health.